SISTEM AGRIBISNIS IKAN PATIN (Pangasius sp) KELOMPOK BUDIDAYA IKAN SEKAR MINA DI KAWASAN MINAPOLITAN PATIN KECAMATAN KOTA GAJAH LAMPUNG TENGAH - Susi Susanti; Dyah Aring Hepiana Lestari; Eka Kasymir (Lampung University, 2017)
This research aims to determine the procurement system of catfish cultivation facilities, the income of catfish cultivation, added value of processing catfish (abon, patty and catfish stick ), the marketing of catfish (fresh and processed), and support services that support the agribusiness system on catfish. This research is a case study, conducted on propose in Kota Gajah Subdistrict of Central Lampung Regency. The data is collected in November 2014. Respondents of this research are 33 person; amongs of them, 20 person are cultivators, 1 processor and 12 traders (9 fresh catfish traders and 3 processed catfish traders). The data, consisted of primary and secondary data,is analyzed by deskriptive qualitative analysis, income analysis, added value and marketing margins. The reasearch result showed that the procurement of feed input did not fulfill the criteria for proper price and proper quality. The average income obtained from the cultivation of catfish MT I was Rp124,303,944.44/ha in which R/C value was 2.66 and on MT II wass Rp165,798,467.59/ha in which R/C value was 2.87. The highest added value of catfish processed was catfish stick with the ratio value of 51.71 percent. Marketing production of fresh catfish Pokdakan Sekar Mina in Kota Gajah Subdistrict, Central Lampung was inefficient, while marketing of processing catfish still simple marketing. Supporting services that supported and facilitated the agribusiness activities of catfish Pokdakan Sekar Mina were market, counselors, transportation, and government regulation. Key words: added value, agribusiness system, catfish